Impact of active learning instruction in blended learning on students' anxiety levels and performance - Li, Bo; Yu, Jiajing; Sun, Lichen; Yang, Hongze (Frontiers in Education, 2024)
Contemporary educational research has extensively explored the link between anxiety and student performance, yet there's a gap in understanding this relationship in classrooms with varying levels of active learning. This study aims to establish connections between instructional design, anxiety levels, and student performance, ultimately creating a comprehensive theoretical framework.This study was conducted during the pandemic.Data from 186 respondents at Northeast Forestry University were collected through an online survey, and 25 students were randomly selected for interviews to gather feedback.In the practical application of the introductory course "Basics Product Design," ，the Rain Class software was used to facilitate an active learning environment.Data from the online survey were organized in SPSS, then imported into the structural model framework in AMOS to calculate fit indices and other values to test hypotheses, applying structural equation modeling.Additionally, the relationship between anxiety levels and student performance was analyzed based on data from five classes using different instructional designs.The results indicated that cold calling was significantly positively correlated with anxiety levels (SE=0.632, P<0.001), group work was significantly positively correlated with anxiety (SE=0.166, P<0.05), clickers were not significantly positively correlated with anxiety (SE=0.188, P>0.05), and anxiety levels were not significantly negatively correlated with student performance (SE=-0.306, P>0.05).Mediation effect tests revealed that anxiety levels fully mediated the relationship between the use of clickers and student performance.Comparing student performance and anxiety levels across the five classes, the relationship between anxiety levels and student performance did not show a simple positive or negative correlation but followed a fluctuating curve,with an interval of anxiety levels that promotes student performance.Conclusion: In a blended learning environment, different designs and frequencies of active learning activities can lead to varying levels of anxiety, ,which in turn affect student performance.One prominent factor in increasing student anxiety is cold calling.The findings can serve as a basis for teachers to design educational plans, helping to create classroom environments that foster active participation and maintain a positive state among students.Furthermore, in this instructional environment, it is worth further investigating the factors influencing student anxiety and the impact of anxiety on student academic performance.